Conservação e uso da variabilidade genética do cajueiro: um estudo sobre a composição nutricional do banco ativo de germoplasma da Embrapa Agroindústria Tropical - Caetano, Ivanize Daniella Elvira (2024)
The cashew nut kernel (ACC) is one of the primary products derived from the cashew tree (Anacardium occidentale L.), renowned for its rich essential nutrient content, and ranks as the third most consumed nut globally. Characterizing cashew genotypes is pivotal for selecting superior varieties that hold promise as protein sources for the burgeoning plant-based market. This study aimed to characterize ACCs from 50 accessions of the Active Cashew Germplasm Bank at Embrapa Agroindústria Tropical. Initially, the assessment encompassed variables such as nut and kernel mass, industrial yield, moisture, protein, lipids, and ash content. Subsequently, the amino acid profile of accessions with the highest protein content was evaluated. The experimental design was entirely randomized, and the obtained data underwent analysis of variance followed by mean grouping testing. To evaluate genotype diversity concerning moisture, lipids, ash, and protein variables, the data underwent multivariate cluster analysis using the hierarchical method of average linkage between groups (UPGMA). Regarding physical parameters, it was noted that among the accessions, nut mass ranged from 4.42 to 15.87g, while kernel mass exhibited variation from 1.37 to 3.73g, and industrial yield varied from 8.53% to 31.36%. In terms of nutritional characterization, moisture content ranged from 2.6% to 3.9%, with ash content varying between 2.6% and 8.1%. Protein content ranged from 13.7% to 22.1%, while lipids ranged from 30.6% to 46.2%. Based on these findings, five accessions with the highest protein content were chosen for characterization of their amino acid profile and, consequently, their protein quality. Among the analyzed amino acids, glutamic acid was the most abundant, ranging from 4.39% to 5.28%, followed by arginine, with a range of 2.21% to 2.63%, and aspartic acid, ranging from 1.89% to 2.24%. Conversely, methionine exhibited the lowest content among the samples, ranging from 0.33% to 0.37%. It's crucial to emphasize that all the accessions exhibited protein of excellent quality, with amino acid concentrations surpassing the thresholds set by Brazilian legislation for declaring nutritional claims related to protein. The nutritional diversity observed in the evaluated cashew nut kernels underscores their richness and potential as a source of high-quality protein. This insight provides valuable information for the selection of superior genotypes, thus contributing to the advancement of research and development in this field.